Examination of learning motivations among students of Szent István Univerity - Kiss, Ádám Gergő (Studia Mundi – Economica, 2015)
From the moment of our birth, we are "doomed" to learn. However, if we do not have sufficient incentive and a sufficient motivation for learning, then there can be no true learning. Therefore, it is important to recognize the motives which are most encouraged us to learn as soon as possible.In my study I use the Academic Motivation Scale adapted by Vallerand et al (1992) among the students of Szent István University to gain a picture of what motivate current students for their studies.